Prevalence of Cryptosporidiosis among Cancer Patients in Sulaimani Province/Iraq - Nasir, Kamaran Ameen; Hama , Abdullah Ahmed; Ali, Salar Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
The intestinal protozoan parasites are common pathogens of the gastrointestinal tract (GIT) and diarrhea among immunocompromised patients. Entamoeba histolytica, Giardia lamblia, and opportunistic Cryptosporidium spp. are considered as the most types of intestinal parasites. Cryptosporidium is an obligate intracellular protozoan microorganism that causes gastrointestinal infection (cryptosporidiosis), which is an opportunistic intestinal parasite among cancer and immunocompromised patients, it is a major cause of life-threating diarrhea among immunosuppressive patients. This study included 365 cases (300 cancer patients and 65 non cancer individuals). The Modified Ziehl-Neelsen (MZN) staining and crypto-strip (Immunochromatographic Assay) techniques were followed for Cryptosporidium oocyst’s detection in human feces. Prevalence of Cryptosporidium species among cancer patients was 17% while among non-cancer patients was 3%. The gender and residency have no significant effect on cryptosporidiosis, the significant differences were observed between cryptosporidiosis cases and stool consistency. However, a relatively higher rate of Cryptosporidiosis was observed among old age (≥ 51 years) with cancer undergoing chemotherapy. This finding concludes that Cryptosporidium spp. are considered as a common diarrheal causative agent among cancer patients and need more care and management.